SENJAKALA TRADISI KENDURIAN DI DESA GRAJEGAN: PERSPEKTIF FENOMENOLOGI AGAMA - Nilawaty, Azzah (Academic Journal of Islamic Principles and Philosophy, 2020)
The study discusses the shift in the Grajegan communityÂ inÂ interpreting theÂ kendurianorÂ kondhangan. Nowadays, fewer Grajegan people practice theÂ kenduriantradition compared to decades ago. This paper explainsthe causative factors in the perspective of religious phenomenology. This is a field research which usesÂ Â participatory observation and interviewto collect the data. The dataÂ isÂ analysedÂ Â usingÂ the symbolic interpretationmethod.Â This research revealsthat there are three factors thatÂ cause theÂ decreaseÂ of theÂ tradition of kendurian in Grajegan. First, theÂ emergeÂ of some religious groups which prohibit theÂ kenduriantradition. Second,Â the reluctance of someÂ families toÂ performÂ theÂ kendurianÂ tradition.. Third, the dependence of the family to theÂ figure ofÂ mother.Â AÂ mother has an important role in the preparation of the feast. If this figureÂ does not exist, theÂ kendurianwhich requiresÂ the preparation ofÂ certain special foodsÂ will not occur.Â